2023
DOI: 10.15252/emmm.202216434
|View full text |Cite
|
Sign up to set email alerts
|

Interferon regulates neural stem cell function at all ages by orchestrating mTOR and cell cycle

Abstract: Stem cells show intrinsic interferon signalling, which protects them from viral infections at all ages. In the ageing brain, interferon signalling also reduces the ability of stem cells to activate. Whether these functions are linked and at what time interferons start taking on a role in stem cell functioning is unknown. Additionally, the molecular link between interferons and activation in neural stem cells and how this relates to progenitor production is not well understood.Here we combine single-cell transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 76 publications
(135 reference statements)
0
5
0
Order By: Relevance
“…There is recent interest in defining the impact of interferons in the SVZ, and recent work has shown an important role of interferons in regulating SVZ NSCs in young and old mice. Type I interferon modulates the activation of SVZ NSCs and induces quiescence ( Kalamakis et al, 2019 ; Carvajal Ibañez et al, 2023 ). At the same time, other groups report major contributions of type I interferon signaling in the aging choroid plexus and ventricular zones ( Baruch et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is recent interest in defining the impact of interferons in the SVZ, and recent work has shown an important role of interferons in regulating SVZ NSCs in young and old mice. Type I interferon modulates the activation of SVZ NSCs and induces quiescence ( Kalamakis et al, 2019 ; Carvajal Ibañez et al, 2023 ). At the same time, other groups report major contributions of type I interferon signaling in the aging choroid plexus and ventricular zones ( Baruch et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, IFN-γ, through activation of its canonical STAT1 pathway, acts specifically on Nestin + progenitors to decrease progenitor proliferation and the number of cycling cells in a normal SVZ ( Pereira et al, 2015 ). Moreover, a recent paper demonstrated type I interferon induces cell cycle arrest and quiescence of SVZ NSCs ( Carvajal Ibañez et al, 2023 ). Still, the transcriptional targets of Stat1 and the direct role of Stat1 in the regenerative program of NSCs in neuroinflammation as seen in MS due to IFN-γ are still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Our SVZ NSC reference lineage is comprised of adult WT SVZ NSCs and progeny from three studies 8,13,14 . We incorporated cells from 15 to supplement our SVZ lineage and compare celltype labels.…”
Section: Methodsmentioning
confidence: 99%
“…Physiological concentrations of IFN-γ notably enhanced neuronal differentiation in vitro [ 33 ]. Moreover, further research indicated that IFN regulates the cell cycle of NSCs by suppressing the expression of SOX2 [ 34 ]. Furthermore, IFN-γ protected NSCs from central nervous system (CNS) infection-related damage through immune-related bystander effects [ 33 ].…”
Section: Introductionmentioning
confidence: 99%